2018
DOI: 10.1002/pmic.201800194
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure, Proteomics and Crystallization of the Limpet Teeth

Abstract: Limpets are marine mollusks that use mineralized teeth, one of the hardest and strongest biomaterials, to feed on algae on intertidal rocks. However, most of studies only focus on the ultrastructure and chemical composition of the teeth while the molecular information is largely unknown, limiting our understanding of this unique and fundamental biomineralization process. The study investigates the microstructure, proteomics, and crystallization in the teeth of limpet Cellana toreuma. It is found that the limpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
(96 reference statements)
1
15
0
Order By: Relevance
“…In this study, we aimed to reveal the shell microstructures and chemical composition of the deep-sea limpet E. crystallina living at a depth of about 2,700 m of the Southwest Indian Ocean Ridge using various material characterization techniques including transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and Fouriertransform infrared (FT-IR) spectroscopy. The TEM characterization is a proficient tool that allows scientists to investigate microstructural images and crystallographic details of nanomaterials (Suzuki et al, 2011;Suzuki et al, 2017;Wang et al, 2018;Ying et al, 2020). The width difference in layered structure between E. crystallina and C. toreuma shells due to their living environment was determined by TEM images.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to reveal the shell microstructures and chemical composition of the deep-sea limpet E. crystallina living at a depth of about 2,700 m of the Southwest Indian Ocean Ridge using various material characterization techniques including transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and Fouriertransform infrared (FT-IR) spectroscopy. The TEM characterization is a proficient tool that allows scientists to investigate microstructural images and crystallographic details of nanomaterials (Suzuki et al, 2011;Suzuki et al, 2017;Wang et al, 2018;Ying et al, 2020). The width difference in layered structure between E. crystallina and C. toreuma shells due to their living environment was determined by TEM images.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies from a materials perspective, the molecular data underlying their formation is scarce. Three studies have used proteomics to reveal 22 , and 15 proteins that are related to chiton teeth and limpet teeth formation, respectively. By transcriptome, the genetic basis of the freshwater snail radula formation was revealed, highlighting a chitin synthase with a myosin motor domain …”
Section: Introductionmentioning
confidence: 99%
“…These incredibly hard minerals in the teeth of limpets demonstrate their utility in scraping rocks for algae. The morphology of goethite have been well studied by microscopy and spectroscopy methods (Mann et al, 1986;Pierre et al, 1986;Sone et al, 2005;Wang et al, 2018). It was found that the tooth base contains microcrystalline(superparamagnetic) and disordered goethite, while the cusp consists of needle-like goethite crystals (Pierre et al, 1986;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of goethite have been well studied by microscopy and spectroscopy methods (Mann et al, 1986;Pierre et al, 1986;Sone et al, 2005;Wang et al, 2018). It was found that the tooth base contains microcrystalline(superparamagnetic) and disordered goethite, while the cusp consists of needle-like goethite crystals (Pierre et al, 1986;Wang et al, 2018). These needle goethites are aligned in the direction of the fibers, and the crystals are smaller in the anterior region and larger in the posterior region (Wal, 1989;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation